The summoning [large type] - Graham, Heather (Graham, Heather. Krewe of hunters., 2019)
When Kristi Stewart inherits a property in the old part of Savannah, she knows it comes with stories of hauntings. But she doesn't believe in ghosts, even while she runs seances for the guests of McLane House Bed-and-Breakfast. Until the inexplicable midnight appearance of one of her infamous ancestors. Terrified, she flees into the night--and right into the arms of Dallas Wicker. Dallas is trying to uncover the truth about a colleague who died under suspicious circumstances. As strange happenings continue to plague Kristi's home, it is soon clear that there's a very living threat in the neighborhood--several people have disappeared without a trace. Dallas can't find any connection between the victims, but someone wanted them gone, and it might be linked to the history of McLane House. And that means Kristi should be very afraid. The Series name is " Krewe of Hunters."